Purine metabolism regulates Vibrio splendidus persistence associated with protein aggresome formation and intracellular tetracycline efflux - Li, Yanan; Wood, Thomas K.; Zhang, Weiwei; Li, Chenghua (Frontiers in Microbiology, 2023)
A small subpopulation of Vibrio splendidus AJ01 that was exposed to tetracycline at 10 times the minimal inhibitory concentration (MIC) still survived, named tetracycline-induced persister cells in our previous work. However, the formation mechanisms of persister is largely unknown. Here, we investigated tetracycline-induced AJ01 persister cells by transcriptome analysis and found that the purine metabolism pathway was significantly downregulated, which was consistent with lower levels of ATP, purine, and purine derivatives in our metabolome analysis. Inhibition of the purine metabolism pathway by 6-mercaptopurine (6-MP, inhibits ATP production), increased persister cell formation and accompanied with the decreasing intracellular ATP levels and increasing cells with protein aggresome. On the other hand, the persister cells had reduced intracellular tetracycline concentrations and higher membrane potential after 6-MP treatment. Inhibition of the membrane potential by carbonyl cyanide m-chlorophenyl hydrazone reversed 6-MP-induced persistence and resulted in higher levels of intracellular tetracycline accumulation. Meanwhile, cells with 6-MP treatment increased the membrane potential by dissipating the transmembrane proton pH gradient, which activated efflux to decrease the intracellular tetracycline concentration. Together, our findings show that reduction of purine metabolism regulates AJ01 persistence and is associated with protein aggresome formation and intracellular tetracycline efflux.